2015
DOI: 10.1039/c5cp04365d
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid density functional study on the visible light photocatalytic activity of (Mo,Cr)–N codoped KNbO3

Abstract: To improve the photocatalytic performance of KNbO3 for the decomposition of water into hydrogen and oxygen, the electronic structure of KNbO3 should be modified to have a suitable bandgap with band edge positions straddling the water redox level so as to sufficiently absorb visible light. Hybrid density functional theory has been used to calculate the electronic structures of pure, N-, Mo-, and Cr-monodoped, and Mo-N and Cr-N codoped KNbO3. In particular, the influence of the relative positions of Mo-N or Cr-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 68 publications
0
45
0
Order By: Relevance
“…In addition, the PDOS analysis of Mo‐doped NaNbO 3 revealed that the VBM consist of O 2p states and the CBM was controlled by Nb 4d and Mo 4d states. In NNd codoped KNbO 3 , the VBM was found to compose of O 2p states and the Nb 4d states contributed to the CBM …”
Section: Recent Progress In the Design Of Semiconductor Photocatalystmentioning
confidence: 99%
“…In addition, the PDOS analysis of Mo‐doped NaNbO 3 revealed that the VBM consist of O 2p states and the CBM was controlled by Nb 4d and Mo 4d states. In NNd codoped KNbO 3 , the VBM was found to compose of O 2p states and the Nb 4d states contributed to the CBM …”
Section: Recent Progress In the Design Of Semiconductor Photocatalystmentioning
confidence: 99%
“…Hydrogen generation by water splitting using semiconductor photocatalysts is a promising approach to develop renewable energy. As a desired water‐splitting photocatalyst, it must have an appropriate bandgap for using visible light . In addition, it must possess suited band alignments, i.e., the valence band maximum (VBM) and conduction band minimum (CBM) must be separately below the O 2 /H 2 O potential and above the H + /H 2 potential .…”
Section: Introductionmentioning
confidence: 99%
“…2D materials ignite increasing interest owning to their intriguing mechanical, thermal, and optical properties. A desired photocatalyst for water splitting must own the conduction band minimum (CBM) above the (H + /H 2 ) reduction level and the valance band maximum (VBM) below the water oxidation level (H 2 O/O 2 ) . With the consideration of the additional overpotential accompanied with the overall water redox processes, the bandgap needed for effective water splitting must be larger than 1.23 eV .…”
Section: Introductionmentioning
confidence: 99%